EUTROPHICATION AND SOLVING EFFORT IN LAKE RAWAPENING, SEMARANG DISTRICT CENTRAL JAVA (A Spasial Approach) - Wuryanta, Agus; Murtiono, Ugro Hari (Universitas Negeri Semarang, 2018)
Lake Rawapening in Semarang regency is one of the priority lakes to be addressed related to eutrophication Ã‚Â issues. High concentration of Nitrogen (N) and Phospor (P) in the water that cause eutrophication of the lake has fueled the high growth of the water hyacinth. The nutrients can come from agricultural land such as irrigated rice field, rainfed and vegetable farms. Objectives of this study were to determine the total amount of nutrients supply from agricultural land on each catchment area of the lake and provide alternative solutions to reduce nutrients concentration. Information of agricultural land can be obtained from Indonesia Topographic Map (RBI) scale of 1:25.000 and updated with SPOT-2 image recorded in July 5, 2006. Surface water samples were taken during the dry and rainy season from agricultural land as much as 3 samples for each agriculture land types, therefore 18 samples were collected. The result shows, Ringin Sub-watershed has the most extensive irrigated rice field (662.94 ha). While, Panjang Sub- watershed has the most extensive of rainfed Ã‚Â (988.49 ha) and vegetable farms (643.74 ha). The agriculture land in the catchment area has supplied N and P nutrients of 2.181,71 tons and 420,04 tons to water of the lake, annually. Panjang river has supplied the highest N and P nutrients, ie 769,025 ton and 105,432 ton annually, while Kedung Ringin river has supplied lowest N and P nutrients, ie 19,479 ton and 4,790 ton, annually. Buffer zone around the lake sould be developed necessary to reduceÃ‚Â the nutrients Ã‚Â supply to the lake.